PROMOTING MULTICULTURAL EDUCATION THROUGH LITERACY IN MADRASAH: Promoting Multicultural Education Through Literacy In Madrasah - Khofifah, Nur; Hidayah, Fathi; Fanani, Ahmad Aziz; Baharun, Hasan (STAI Ma'had Aly Al-Hikam Malang, 2024)
ABSTRAK This research evaluates the implementation and effectiveness of multicultural education strategies in schools in Jakarta, Indonesia. The main objectives of the research are to identify the obstacles faced in the development and implementation of a multicultural curriculum, assess the impact of multicultural literacy activities on students' knowledge and attitudes, evaluate the role of partnerships between schools, parents, and communities, and examine the optimization of digital platforms in multicultural teaching. This research uses a qualitative approach with descriptive methods. Data was collected through in-depth interviews, participant observation, and document analysis at the research site at Madrasah Ibtida'iyah Negeri 1 Banyuwangi. The research results show that the multicultural curriculum positively impacts students' understanding and attitudes towards cultural diversity. Multicultural literacy activities and partnerships with parents and communities strengthen inclusive attitudes and respect for differences among students. Additionally, using digital technology in multicultural teaching increases student interest and engagement. The implications of this research emphasize the importance of a holistic approach that integrates various strategies to create an inclusive learning environment and support cultural diversity. This research provides an empirical basis for developing more effective multicultural education policies and practices in Indonesia. Penelitian ini mengevaluasi implementasi dan efektivitas strategi pendidikan multikultural di sekolah-sekolah di Jakarta, Indonesia. Tujuan utama dari penelitian ini adalah untuk mengidentifikasi hambatan yang dihadapi dalam pengembangan dan implementasi kurikulum multikultural, menilai dampak kegiatan literasi multikultural terhadap pengetahuan dan sikap siswa, mengevaluasi peran kemitraan antara sekolah, orang tua, dan masyarakat, serta mengkaji optimalisasi platform digital dalam pengajaran multikultural. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan analisis dokumen di lokasi penelitian di Madrasah Ibtida'iyah Negeri 1 Banyuwangi. Hasil penelitian menunjukkan bahwa kurikulum multikultural berdampak positif terhadap pemahaman dan sikap siswa terhadap keragaman budaya. Kegiatan literasi multikultural dan kemitraan dengan orang tua dan masyarakat memperkuat sikap inklusif dan penghargaan terhadap perbedaan di antara para siswa. Selain itu, penggunaan teknologi digital dalam pengajaran multikultural meningkatkan minat dan keterlibatan siswa. Implikasi dari penelitian ini menekankan pentingnya pendekatan holistik yang mengintegrasikan berbagai strategi untuk menciptakan lingkungan belajar yang inklusif dan mendukung keragaman budaya. Penelitian ini memberikan dasar empiris untuk mengembangkan kebijakan dan praktik pendidikan multikultural yang lebih efektif di Indonesia. Keywords: Multicultural Education, Multicultural Literacy, Inclusive Curriculum